HUBUNGAN KONDISI FISIK RUMAH DAN PERILAKU KELUARGA TERHADAP KEJADIAN ISPA PADA BALITA DI KELURAHAN CAMBAI KOTA PRABUMULIH TAHUN 2010 - Della Oktaviani; Nur Alam Fajar; Imelda G Purba (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
The Acute Respiration Tract Infection (ARTI), is one of the main caused of sickness at under five years old children in a developing country. The aim of this research is to know the correlation between the physical condition of the house which is including the roof, the floor, the wall, the ventilation, the capacious of the floor, the density of the people at the house, the recycle bin, and the family attitude (knowledge and the family attitude) to the Acute Respiration Tract Infection (ARTI). The research is done on May, 2010 In Cambai district. The kind of the research is observational with cross sectional approach. The subject is taken from the houses which there is under five years old with totally 82 respondents. The sample is taken by random sampling technique. The statistich which used is chi square with SPSS 17th program. The result of the research showed that there is correlation between knowledge and the family attitude (p= 0,049), the roof (p=0,010), the floor (p=0,000), the house ventilation (p=0,046), the capacious of the floor and the density of the people at the house (p=0,032) to the Acute Respiration Tract Infection(ARTI), on the other hand, the wall of the house (p=0,299),and the recycle bin (p=0,068) no correlation to the ARTI. According to the result of research, we can conclude that the Acute Respiration Tract Infection to the Under Five Years Old Children except influenced by knowledge and the familyattitude also influenced by the physical of the condition of the house (roof, floor, ventilation, the capacious of the floor, and the density of the people at the house). The suggestion which submit to prevent and to reduce the Acute Respiration Tract Infection to the under five years old children is to increase the healthy attitude is needed such as no smoking at home or the public society about the healthy house requirement in order that the prevention could be done.